Sistem Penjualan Pakaian Online "tukuCALAMBY" - Anjar Septinegara; Freshma Neda Cisya Tama; Isyatin Rodliyati Karima; Kartika Imam Santoso; Dhika Malita Puspita Arum (Julia: Jurnal Ilmu Komputer An Nuur, 2025)
The development of information and communication technology has changed the way consumers shop, especially in the fashion and clothing industry. This study aims to develop an online clothing ordering system called “tukuCALAMBY.” This system is useful for improving the efficiency of the sales process and providing convenience for customers when shopping. The system is designed using a web-based approach with two main actors, namely the admin and the customer. The system development method employs the Software Development Life Cycle (SDLC) approach using the Waterfall model by Sommerville. The design utilizes system modeling with the Unified Modeling Language (UML). The development results demonstrate that the “tukuCALAMBY” system successfully integrates features for managing product data, ordering, payment, and reporting into a single user-friendly platform. This system provides an effective solution to expand market reach and improve operational efficiency for online clothing stores. User Acceptance Testing (UAT) involving 20 users yielded a testing result of 92%.